Engagement of older persons in cultural activities: importance and barriers - Ghenta, Mihaela; Bobarnat, Elen-Silvana (Journal of Economic Development, Environment and People, 2019)
The aim of this article is to present the importance of cultural activities for older person, as well as of the barriers related to engagement in such activities. Cultural activities involvement is recognized as a way to promote the social participation of older persons and thus it contributes to a better social inclusion of these persons. The first part of the paper points the importance of cultural activities among older Romanians, while the last part of the article presents the factors that limit a more engagement in such activities for people of age 65 years and over